Special Issue in Honor of Dr. Marie-Hélène Metz-Boutigue 75th Birthday: "Recent Advances in Multifunctional Antimicrobial Peptides as Preclinical Therapeutic Studies and Clinical Future Applications" - Francesco, Scavello; Mohamed, Amiche; Ghia, Jean-Eric (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Pharmaceutics is very pleased to be hosting a Special Issue in honor of Dr. Marie-Hélène Metz-Boutigue, acknowledging her influential scientific contributions to research on Antimicrobial Peptides (AMPs). This Special Issue aimed to gather and highlight significant advancements for AMPs as an alternative to antibiotics for increasing resistant strains and recent discoveries for future therapeutic approaches. Since the AMPs are multifunctional peptides with antitumor and immunomodulating effects, original research articles and reviews in these fields were particularly welcomed. Manuscripts regarding antimicrobial biomaterials including AMPs were also of interest.